BRAF and NRAS mutations in circulating Langerhans-like CD1a+ cells in a patient with pulmonary Langerhans' cell histiocytosis. Issue 4 (12th October 2017) - Zhang, Li; Pacheco-Rodriguez, Gustavo; Steagall, Wendy K.; Kato, Jiro; Colby, Thomas V.; Haughey, Mary; Moss, Joel
Pulmonary Langerhans' cell histiocytosis (PLCH) presents as accumulation of Langerhans' cells and other langerin-expressing dendritic cells (LCH cells) in the lungs that cause bilateral nodules and cavities, which are generally restricted to the upper lung fields of adult cigarette smokers [1–3]. The PLCH lung nodules appear to be the origin of the cavities, which could also have a cyst-like appearance that gives rise to a differential diagnosis that includes both cavitary and cystic lung diseases [3]. A characteristic histopathologic feature of PLCH is destruction of the wall of distal airways by infiltration of LCH cells [3]. Given the cellular aetiology, it has been proposed that LCH, and specifically PLCH, might represent a neoplastic or reactive condition [4, 5]. Currently, the diagnostic criteria of LCH include the demonstration of CD1a- and CD207-positive LCH cells in the LCH lesions [6]. As a lipid-presenting molecule, CD1a is abundantly expressed on langerin-expressing cells and accumulates in Birbeck granules, where it colocalises with langerin [6]. The BRAF mutations in LCH, including PLCH cases, were detected in 38% to 64% of LCH lesions in two independent studies [7, 8]. Recently, Mourah et al . [9] presented the remarkable finding that NRAS, in addition to BRAF mutations, occur in PLCH lesions. The findings of an abnormal cell and an oncogenic mutation are consistent with the proposal that LCH is a neoplastic disease. Detection of BRAF and NRAS in Langerhans-like cells from a patient with pulmonary Langerhans' cell histiocytosis http://ow.ly/cCDG30f0TcT